THE EFFECT OF ALLOY COMPOSITION ON MICROHARDNESS AND ELECTROCHEMICAL CORROSION ON NI-TI-NB SHAPE MEMORY ALLOYS - QADIR, HUSSEIN AHMED (Fırat Üniveristesi, 2022)
Bu tez, dört farklı oranda niyobyumun (Nb) içeren NiTi alaşımının bazı fiziksel ve kimyasal özellikleri araştırmıştır. Çeşitli sıcaklıklarda termal döngünün bazı termodinamik parametreler üzerindeki etkisi de değerlendirilmiştir. Numune üretimi indüksiyon eritme fırını kullanılarak gerçekleştirilmiştir. Nb katkısının dönüşüm sıcaklıkları ve Ni-Ti-Nb şekil hatırlamalı alaşımların(SHA) termal parametreleri üzerindeki etkisi, farklı ısıtma hızları ile diferansiyel tarama kalorimetrisi (DSC) kullanılarak araştırıldı. SEM-EDX kullanılarak malzemelerin mikroyapısal özelliklerini araştırıldı. Tüm numunelerin mikrosertliğini değerlendirmek için Vickers mikrosertlik tekniği uygulandı. Hem Nb katkısı hem de termal döngü, dönüşüm sıcaklıklarını ve entalpi değişimi, entropi değişimi, elastik enerji ve Gibbs serbest enerjisi gibi termodinamik parametreleri azalttı, ancak martensitik faz dönüşümünün sıcaklık histerezisini arttırdı. Nb ilavesi, NiTi alaşımının mikrosertliğini arttırırken aktivasyon enerjisini azaltmıştır. Korozyon direnci test sonuçları ayrıca Nb'nin SHA'ların korozyon direncini artırarak Ni-Ti alaşım biyouyumluluğunu iyileştirmede olumlu bir etkiye sahip olduğunu göstermiştir.

This theis investigated the effects of four varying quantities of niobium (Nb) on some physical and chemical properties of Ni-Ti alloy. The effect of thermal cycling at various temperatures on some thermodynamic parameters was also evaluated.The sample manufacturing procedure was carried out using the Induction melting furnace. The effect of the Nb additive on transformation temperatures and different thermal parameters of Ni-Ti-Nb SMAs was investigated using differential scanning calorimetry (DSC) with different heating rates. SEM was also used to investigate the microstructural properties of materials, and the Vickers microhardness technique was performed to evaluate the microhardness of all samples. Both Nb additive and thermal cycling decreased transformation temperatures and other thermodynamic parameters such as enthalpy change, entropy change, elastic energy, and Gibbs free energy, but it increased the temperature hysteresis of the martensitic phase transformation. The addition of Nb decreased the activation energy while increasing the microhardness of the Ni-Ti-Nb alloy. The corrosion resistance test results also showed that Nb has a positive effect on improving Ni-Ti alloy biocompatibility by increasing the corrosion resistance of the SMAs.
Ni-Ti-Nb şekil hafızalı alaşımlarda alaşım komposizyonunun mikrosertlik ve elektrokimyasal korozyona etkisi
Keywords: Fizyoloji